Delay in Breast Cancer: Implications for Stage at Diagnosis and Survival - Caplan, Lee (Frontiers in Public Health, 2014)
Breast cancer continues to be a disease with tremendous public health significance. Primary prevention of breast cancer is still not available, so efforts to promote early detection continue to be the major focus in fighting breast cancer. Since early detection is associated with decreased mortality, one would think that it is important to minimize delays in detection and diagnosis. There are two major types of delay. Patient delay is delay in seeking medical attention after self-discovering a potential breast cancer symptom. System delay is delay within the health care system in getting appointments, scheduling diagnostic tests, receiving a definitive diagnosis, and initiating therapy. Earlier studies of the consequences of delay on prognosis tended to show that increased delay is associated with more advanced stage cancers at diagnosis, thus resulting in poorer chances for survival. More recent studies have had mixed results, with some studies showing increased survival with longer delays. One hypothesis is that diagnostic difficulties could perhaps account for this survival paradox. A rapidly growing lump may suggest cancer to both doctors and patients, while a slow growing lump or other symptoms could be less obvious to them. If this is the case, then the shorter delays would be seen with the more aggressive tumors for which the prognosis is worse leading to reduced survival. It seems logical that a tumor that is more advanced at diagnosis would lead to shorter survival but the several counter-intuitive studies in this review show that it is dangerous to make assumptions.